The Effect of Pop Up Book for Students’ on Vocabulary Mastery - Sri Wahyuni Nasution; Fitri Rayani Siregar; Sri Minda (Lentera Ilmu: Jurnal Kependidikan, Riset dan Teoritis, 2024)
This research was aimed to find out whether learning by using Pop-up book significantly effects on students’ vocabulary, or not. This research is quantitative method in pre experimental method. This research uses one group pre-test and post-test design. The instrument was used test. According to the result of the test, it was found that the students’ score before learning by using pop-up book in SMP Negeri 1 Ujung Batu was classified to enough. The students’ score after learning by using pop-up book in SMP Negeri 1 Ujung Batu was classified as good. So there was a significant effect using Pop-up book on students’ vocabulary Mastery at grade VII SMP Negeri 1 Ujung Batu.